2018
DOI: 10.1371/journal.pone.0205279
|View full text |Cite
|
Sign up to set email alerts
|

Older adult fall prevention practices among primary care providers at accountable care organizations: A pilot study

Abstract: BackgroundFalls are a serious and common problem among older adults. Low-tech, inexpensive, community-based fall prevention programs have been shown to be both effective and cost effective, however, these programs are not well-integrated into clinical practice.Research designWe surveyed primary care providers at a convenience sample of two accountable care organizations in Massachusetts to assess their beliefs, attitudes, knowledge, and practices relative to fall risk assessment and intervention for their olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
0
28
1
Order By: Relevance
“…There have been no trials of telerehabilitation focused on preventive rehabilitation for general elderly people. In addition, at present, the quality of the rehabilitation is not secured [32]. The present study suggests that our telerehabilitation system is a feasible option for the rehabilitation of elderly people in rural areas.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…There have been no trials of telerehabilitation focused on preventive rehabilitation for general elderly people. In addition, at present, the quality of the rehabilitation is not secured [32]. The present study suggests that our telerehabilitation system is a feasible option for the rehabilitation of elderly people in rural areas.…”
Section: Discussionmentioning
confidence: 74%
“…Recent meta analyses and systematic reviews revealed the e cacy of fall prevention intervention in community-dwelling older people [28][29][30][31]. Community-based fall prevention interventions are low cost and low-tech programs, which can achieve a 25-30% reduction in falls per year after the program [32]. Thus, the e cacy of conventional fall prevention intervention has been well recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STEADI offers resources for health care providers to assess and minimize fall-related risk factors such as medications linked to falls, home hazards, sensory impairment, and chronic conditions [8]. While originally developed for use in primary care, engagement has remained low in this setting [9,10]. With rising prescription medication use, polypharmacy, and patients receiving care from numerous providers [11,12], there is a distinct need for the expertise of a pharmacist to help manage medication-related fall risk.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that the majority of general practitioners do not specifically assess older patients' risk of falls unless a fall has already occurred (Wenger et al, 2003, Jones et al, 2011, Grant et al, 2015, Kielich et al, 2017, Mackenzie and McIntyre, 2019 and there is a general lack of awareness and use of recognised clinical guidelines and programmes (Jones et al, 2011, Howland et al, 2018. It is, however, reassuring that fall risk screening and fall reduction behaviours among primary care providers can be significantly improved through various interventions (Brown et al, 2005, Wenger et al, 2009, Tricco et al, 2019.…”
Section: 3: Challenges In Implementing Fall Risk Assessment and Redmentioning
confidence: 99%